The Impact of OCA2 (rs1800407) and HERC2 (rs12913832) Gene Polymorphisms on Iris Color in a Sample of Iraqi People - Tabarek Mundher Noaman; Abdul Kareem A. Alkazaz (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study was directed in order to determine Single Nucleotide Polymorphisms (SNPs) (rs1800407 G>A)of OCA2 and (rs12913832 A>G) HERC2 genes and their association as a DNA marker with eye color in 60samples of Iraqi people. Samples were collected from College of Science / University of Baghdad and alsopeople from different areas of Baghdad, Iraq; during the two months period from September to November2020. These SNPs determination was carried out by using quantitative real-time polymerase chain reaction(qPCR) of blood samples. The results of rs12913832 genotype showed significantly differences (p<0.05) inthe green eye color group. A Survey of HERC2 gene SNP genotypes and allele frequencies in the black andgreen iris groups showed that there was a significant variation in the wild type (AA) and homozygous mutant(GG) genotype frequencies in (rs 12913832), while the SNP (rs1800407) of OCA2 concluded that gene mayhave a non-significant effect among a sample of this study comparing with green eye to black eye color.